Breeding biology of Bewick's Swans Cygnus bewickii in Chukotka, Far Eastern USSR - Kondratiev, A Ya (Wildfowl, 2013)
Results of long-term research into the breeding biology of Bewick’s Swans in the tundras of Chukotka are presented. The birds usually begin breeding at the beginning of June, 10-16 days after arriving in the breeding sites. Clutch size occasionally numbers 6 eggs, and averages 3.84. Both members of the pair incubate, keeping the clutch warm almost all of the time. The male incubates for 20-50% of the time during the 30 day incubation period. The weight of the newly hatched young varies from 165 g to 197g, withan average of 177.5 g (63.1-67.1% of the weight of the recently laid eggs). The average brood size is 3.40 just after hatching and 2.96 before the young fledge. Young Bewick’s Swans are able to fly in early September when they are 45-50 days old.